Relationship of socio-demographic characteristics of women fish vendors and profitable fish vending. - Seville, Ma. Sonnette V. (1998.)
This descriptive study on the women fish vendors of the Iloilo City Central Market focuses on how profitability might be influenced by highest educational attainment, years of experience in trade and membership in credit cooperatives. The subjects are twenty registered women fish vendors of the Iloilo City Central Market. Descriptive statistics employed are measures of central tendency like means, median and mode. Inferential statistics is the chi-square test for independence set at .05 alpha. Generally, the women fish vendors of the Iloilo City Central Market are not members of credit cooperatives, even those who are members, majority of the respondents have at least reached secondary level of education, most of the women fish vendors have been into fish vending for more than five years; and they earn at least P150.00 daily. There are no significant relationship between highest educational attainment and membership in credit cooperatives. However, there is a relationship between years of experience in trade and profitable fish vending.
Thesis (Undergraduate, Bachelor of Arts in Sociology) College of Arts and Sciences, University of the Philippines in the Visayas, Miagao, Iloilo.
Keywords: Fish Vendors -- Women